Advances in Resilient and Sustainable Transport: Proceedings of the 6th Interdisciplinary Conference on Production, Logistics and Traffic 2023 - Clausen, Uwe (Springer, 2024)
This book provides a timely snapshot of research and developments concerning freight and public transport, cargo bikes, maritime and rail transport, electrical and hydrogen vehicles, simulation and optimization in production and logistics, production and supply chain management, sustainable logistics, and intralogistics and automation.